Strategy for Strengthening Public Accountability Through the Implementation of Financial Accounting Standards to Increase National Zakat Payer Participation - Leni Nopilia (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
The strategy for strengthening public accountability through the implementation of the latest financial accounting standards has become a crucial instrument in rebuilding public trust toward national zakat management institutions. This policy article aims to formulate tactical steps to address low financial reporting compliance and weak internal control systems that have historically hindered institutional transparency. The policy methodology employed involves a descriptive qualitative approach through the analysis of regulatory documents, observation of financial statement audit patterns, and evaluation of competency gaps among field practitioners. Problem prioritization was conducted using the USG (Urgency, Seriousness, Growth) analysis, which determined that the weakness of public accountability and financial audits is the most pressing issue to be addressed due to its serious impact on the decline of public participation. The results of the discussion indicate that the primary barriers to adopting these accounting standards include the limitations of fragmented information technology systems and the low number of professionally certified amils. Furthermore, a significant information asymmetry was found between fund managers and zakat payers due to the absence of regular audit mechanisms at the regional level. As a strategic solution, this article recommends that the government, through the Ministry of Religious Affairs, issue regulations mandating external and Sharia audits as a mandatory requirement for the renewal of operational licenses for zakat institutions. Additionally, it is necessary to accelerate the digitalization of nationally integrated accounting systems and strengthen human capital through continuous professional certification programs. The implementation of these recommendations is expected to create a professional and transparent Islamic philanthropy ecosystem, thereby mitigating the risk of fund misappropriation while significantly driving increased public participation in supporting national economic welfare through accountable zakat distribution